Karyotypes of South American species of the Morelloid and Dulcamaroid clades (Solanum, Solanaceae) - Moyetta, Natalia Rita (2013)
A karyotypic study on South American representatives of the Morelloid and Dulcamaroid clades of Solanum was conducted to contribute to a better understanding of their relationships. Mitotic chromosomes of 26 species were examined (13 of which were previously unknown). All taxa presented 2n = 2x = 24 and had small chromosomes (less than 4 μm long) with the exception of S. crispum. Most species displayed symmetrical karyotypes, being 78% and 69% m, 19% and 25% sm and 3% and 6% st for the Morelloid and Dulcamaroid clades, respectively. Solanum crispum (Dulcamaroid clade) was unique by having mostly sm chromosomes and S. sinuatirecurvum (Morelloid clade) stood out with four st pairs and an exclusive pair of satellites in long arms. Solanum tripartitum was the sole entity exhibiting an sm pair with satellites. Most examined species of these clades resulted karyologically indistinguishable, based on conventionally stained mitotic chromosomes. Molecular analyses are needed to gain a better knowledge of the possible karyoevolutionary trends of both clades.